2009
DOI: 10.1007/s12028-009-9289-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation is Influenced by Carbon Dioxide Levels in Patients with Septic Shock

Abstract: According to these data, CA is impaired in the majority of patients with septic shock, especially in the presence of hypercapnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 70 publications
1
54
1
2
Order By: Relevance
“…Similar discrepancies were detected in cerebral autoregulation studies performed among septic patients; although Matta and Stow [5] could not prove any autoregulatory disturbances in the brain circulation of septic patients, Smith et al [13] as well as Pfister et al [14] demonstrated disturbed autoregulatory responses in SAE. In septic shock, Taccone et al [15] reported on impaired cerebral autoregulatory response that seemed to be influenced by hypercapnia. To explain these conflicting results, small sample sizes of the studies and differences in timing of the vasoreactivity tests and in the severity of sepsis have been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar discrepancies were detected in cerebral autoregulation studies performed among septic patients; although Matta and Stow [5] could not prove any autoregulatory disturbances in the brain circulation of septic patients, Smith et al [13] as well as Pfister et al [14] demonstrated disturbed autoregulatory responses in SAE. In septic shock, Taccone et al [15] reported on impaired cerebral autoregulatory response that seemed to be influenced by hypercapnia. To explain these conflicting results, small sample sizes of the studies and differences in timing of the vasoreactivity tests and in the severity of sepsis have been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…45 The implied loss of micro circulatory regulation and function is supported by evidence from studies that used either imaging 16 or nonimaging methods. 8,9 The molecular changes that underlie perturbations of microcirculatory function can be imaged. Molecular MRI techniques using iron oxide particles conjugated to probes such as monoclonal antibodies can create localized paramagnetic changes that are observed on imaging.…”
Section: Endothelial Activationmentioning
confidence: 99%
“…2,[7][8][9] These 'direct' effects of SAEassociated inflammation can be compounded by the 'indirect' effects of such processes on extracranial physiology. For example, hypotension and hypoxia, which are often observed in severe sepsis, can cause independent neurological injury and compound the consequences of primary cerebral pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…However, these guidelines do not consider pre-morbid values and/or mean perfusion pressure (MPP), defined as the difference between MAP and CVP. Yet the difference between pre-morbid values and those achieved during management of septic shock (MAP or MPP deficit) may be an important determinant of renal blood flow and function [3][4][5][6][7][8] and may contribute to subsequent acute kidney injury (AKI).…”
Section: Introductionmentioning
confidence: 99%